Squamous Cell Carcinoma (SCC) of the Oral Cavity: Evolving Patterns - Gehani, Rafa El; Goteti, Saravana HL (Medical Science: Trends and Innovations Vol. 7, 2025)
Background: Squamous cell carcinoma (SCC) comprises 85-90% of all malignancies involving the oral cavity and is prevalent in young adults (\(\le\)40 years) and rare in paediatric subjects (<20 years). Recent interest in understanding the demographic distribution and pattern of SCC in young adults is being performed presently with little literature on SCC in paediatric patients. Objective: The aim of this study was to evaluate the incidence of squamous cell carcinoma in the oral cavity, its risk factors, site, and age of occurrence. Materials and Methods: One hundred and nine cases of squamous cell carcinoma involving the oral cavity were retrieved from the records of the Regional Cancer Centre, Benghazi and were analysed. All patients \(\le\)40 years of age were categorised “as young” to make the results comparable with other publications. Results and Conclusion: The age range was 11–94 years with a male-female ratio of 1.9-1. The tongue (30.2 %) was the most common site of occurrence. Tobacco was found as a risk factor in male patients above 40 years old, however, no risk factors were found in other patients. Due to the changing trends of cancer patterns and associated risk factors, emphasis is placed on the need for an exhaustive evaluation to understand the biology and the role of non-conventional risk factors. Preventive measures and awareness campaigns should be arranged by international agencies and government authorities.